LIBRARY OF DAGESTAN SCHOLAR AND EDUCATOR ISMAILDIBIR FROM SHULANI (1863–1912) - Alibekova, Patimat Magomedovna (History, Archeology and Ethnography of the Caucasus, 2019)
The Dagestan enlightenment of pre-Soviet time is a unique, large-scale and multidimensional phenomenon. Dagestan scientists carry out a lot of scientific work, covering this topic in their research. The historical period of the second half of the XIX - the beginning of the XX century in Dagestan is characterized by the rapid development of the printing industry, educational movement and scientific thought. Muhammad Mavraev, Abusufyan Akayev, Ali Kayayev, Ismaildibir from Shulani and other Dagestan scientists, their number is great, contributed to the cultural development of the country. The task of studying the cultural heritage of the Dagestan peoples remains relevant.There are no special studies in the scientific literature devoted to Ismaildibir, one of the active figures in the field of education, a scientist and a talented poet. To draw up a creative portrait of the scientist and explore his book heritage, we made a scientific trip to the Shulani village in Gunib district of Dagestan. This article covers the results of archeographic work at the Ismaildibir Library. The article provides information about the life and activity of the Dagestan scholar and educator Ismaidibir from Shulani and describes handwritten and old-print works from his book collection. There are no special scientific works dedicated to Ismaildibir, one of the active figures in the field of education, a scientist and a talented poet. The descriptions of the books include the verified data on authors, works, translations of out-of-text records, output data. The Ismaildibir Library from Shulani attests to the diverse scientific interests of its owner. Ismaildibir was available both handwritten works by Arab authors, and texts published in lithographic and typographical ways by medieval authors, and comments, supracommentaries written by scientists, his contemporaries. The significance of this scientist not only in his scientific work but also in the fact that he was an active propagandist of knowledge, an educator. He saw his mission to popularize secular and spiritual knowledge, to promote Islamic values. In the article, we sought to show the image of the Islamic scientist who developed in Dagestan in the second half of the Х1Х - the beginning of the 20th century.
Keywords: Dagestan scholar Abu Ishaq Ismaildibir; Islamic sciences; Arabic manuscripts; oriental old printed books.